Cohort profile: the Jundiaí Zika cohort (JZC), a pregnancy and birth cohort in São Paulo state, Brazil - Nuria Sanchez Clemente; Rosa Estela Gazeta; Manoela Rodrigues; Ana Paula Pascalicchio; Danila Vedovello; Elizabeth B Brickley; Marcia F De Almeida; Saulo D Passos (BMJ Open)
Purpose The Jundiaí Zika Cohort (JZC) is a prospective pregnancy and birth cohort setup in the State of São Paulo, Brazil, to investigate the epidemic of cases of microcephaly and other neurological disorders, presumed to be associated with Zika virus (ZIKV) infection.Participants A total of 748 women with high-risk pregnancies were recruited in the period of March 2016 to August 2017.Findings to date Baseline sociodemographic and medical data were collected at recruitment from 737 pregnant women. Biological samples (ie, blood, saliva and urine) were collected from 695 of the pregnant women (94.3%), of whom 53 (7.6%) were ZIKV-positive on subsequent testing by reverse transcription polymerase chain reaction (RT-PCR) in urine. Biological sample (ie, blood, saliva, urine and cerebrospinal fluid) were collected within 10 days of birth from 409 (57.4%) of the liveborn infants, of whom 19 (4.6%) were ZIKV-positive on subsequent testing by RT-PCR in urine. All remaining biological specimens, as well as colostrum, umbilical cord and placental samples, have been stored in a secure biorepository. Antenatal and postnatal imaging studies and neonatal anthropometry were carried out.Future plans The JZC provides a unique data set which will continue to be explored to study the effects of pregnancy comorbidities on Zika virus infection during pregnancy, the long-term outcomes of children with congenital Zika infection and how physiotherapy and group interventions can improve outcomes for congenitally-infected children. All women in the cohort have reached the end of their pregnancy and currently the oldest children are 2 years old. The study will continue until all the children reach their third birthday (April 2021).